Creación de una microempresa de decoraciones para eventos - Franco Solís, Alex José (2020)
ALEX FRANCO DECORACIONES is a company that will always seek to fulfill its commercial objective, developing commercial strategies and tactics that allow it to achieve that and above all, reach all those people who are willing to hold an event, seeking not only their well-being but also that of The entire community, bearing in mind the responsibility it carries out when meeting the demands of a social environment such as the current one, and that clients feel satisfied and satisfied with the work carried out. One of the fundamental objectives of the company is to establish an interest in art and thus adopt it as a way of life that generates economic dependencies; recognizing the home as a source of decoration that lends itself to any of our products, since we have a variety of these, providing complete assurance of its good acceptance in society.